Carbon Stock Assessment of Nueva Vizcaya State University (NVSU)-Agricultural Innovation Center (AIC), Singian Hills, Tuao South, Bagabag, Nueva Vizcaya - Polo, Camille Jade M.; Cosep II, Patricio A.; Lupaas, Diana M.; Abrias, Norbert; Gandia, Kathrina Mae M.; Vallesteros, Shierel F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the carbon stock at the Nueva Vizcaya State Uni-versity Agricultural Innovation Center in Singian Hills, Tuao South, Bagabag, Nueva Vizcaya. The study covered a 100% inventory of trees with a diameter at breast height of at least 10 centimeters and above. Brown’s formula was used to compute the carbon stock of the species. Trees with a diameter at breast height of less than 70 cm and greater than 70 cm were computed separately. A total of 383 trees with 39 tree species were found in the area. It was found that a total of 910,460.10 kilograms was being sequestered equivalent to 564, 485.26 kilogram of carbon stock. The most abundant and recorded as the largest in terms of diameter breast height in the area is the Rain tree (Samanea saman) followed by Gmelina (Gmelina arborea) and Mangga (Mangifera indica). The rain tree that has the largest diameter breast height has a record of 119 cm with an aboveground biomass of 16,107.45 kg and a carbon stock of 9,986.62 kg. The study concludes that increasing tree volume leads to greater carbon dioxide seques-tration, emphasizing the importance of tree planting and forest con-servation for climate change mitigation and addressing global warm-ing.